Pengaruh Campuran Ekstrak Etanol Buah Pare dan Biji Pinang Terhadap Kadar Testosteron Tikus dengan Menggunakan Metoda ELISA - Sofia, Vivi; Rahmawanti, Salsabila (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Testosterone is a hormone that plays an important role in sexual development and reproductive function. Infertility problems, decreased libido and erectile dysfunction are closely related to decreased testosterone levels in the blood. This study aims to see the effect of a mixture of ethanol extracts of bitter melon (Momordica charantia L.) and areca nut (Areca catechu L) on testosterone levels in male white rats. This study used the Sexual Behavior method. 30 Wistar rats were divided into 5 groups consisting of distilled water control, positive control (X-Gra®) 45 mg/kg BW, ethanol extract of bitter melon (EEBP) dose of 100 mg/kg BW, ethanol extract of areca nut (EEP) dose of 50 mg/kg BW and mixed group of EEBP:EEP (1:1), after 15 days, blood samples were taken and testosterone levels were analyzed. The data obtained were statistically analyzed with one-way ANOVA test and continued with Tukey's HSD test with 95% confidence level (p<0.05) using SPSS ver.20 software. The results showed that testosterone levels in the EEBP group at a dose of 100 mg / kg BW and a mixture of EEBP: EEP (1: 1) of 2.31 ± 0.84 ng/ml and 1.65 ± 0.54 ng/ml were not significantly different when compared to the distilled water control group (p < 0.05). Testosterone levels in the EEP group at a dose of 50 mg/kg BW of 3.43 ± 0.98 ng/ml showed a significant difference with the aquades control group (p<0.05). The mixture of bitter melon ethanol extract at a dose of 100 mg/kg BW and areca nut seeds at a dose of 50 mg/kg BW was not able to increase testosterone levels, while the ethanol extract of areca nut seeds given singly at a dose of 50 mg/kg BW could increase testosterone hormone levels in male white rats. Based on the results obtained in this study, it can be concluded that a mixture of bitter melon ethanol extract at a dose of 100 mg / kg BW and areca nut seeds at a dose of 50 mg / kg BW is not able to increase testosterone levels, while areca nut ethanol extract given singly at a dose of 50 mg / kg BW can increase testosterone levels in male white rats.